Electrochemical and Spectroscopic Studies of Zinc Acetate in 1‐Ethyl‐3‐methylimidazolium Acetate for Zinc Electrodeposition. Issue 4 (12th January 2016) - Ghazvini, Maryam Shapouri; Pulletikurthi, Giridhar; Lahiri, Abhishek; Endres, Frank
Abstract: In this paper, we report on the electrodeposition of zinc from the ionic liquid 1‐ethyl‐3‐methylimidazolium acetate ([EMIm]OAc) with various concentrations of zinc acetate [Zn(OAc)2 ] at 100 °C. The electrochemical behavior of zinc complexes in [EMIm]OAc was determined by cyclic voltammetry. Raman and infrared spectroscopy were employed to study the coordination of Zn 2+ ions with OAc −, and it was found that upon increasing the Zn(OAc)2 concentration the intensity of the band for the free acetate anion weakened, due to binding with Zn 2+ ions. A minimum concentration of 4 m Zn(OAc)2 was required to observe bulk zinc deposition, and in that case, the reducible species present in the solution were probably a mixture of Zn(OAc)2 and Zn(OAc) + . Furthermore, the scanning electron microscopy results revealed microcrystals of zinc composed of many nanostructures distributed on the substrate, and X‐ray diffraction analysis indicated that a Zn–Au alloy along with Zn films was obtained. Abstract : Solvation matters : Electrodeposition of zinc from 1‐ethyl‐3‐methylimidazolium acetate with various concentrations of Zn(OAc)2 is studied. Spectroscopic analysis shows that upon increasing the Zn 2+ ion concentration, the coordination number to form reducible species decreases.